Barriers to adequate nutrition care for child malnutrition in a low-resource setting: Perspectives of health care providers - Elhady, Ghada Wahby; Ibrahim, Sally kamal; Abbas, Enas S.; Tawfik, Ayat Mahmoud; Hussein, Shereen Esmat; Salem, Marwa Rashad (Frontiers in Public Health, 2023)
Abstract Introduction: Several studies in developing countries found that more need-based training is required for health care providers (HCPs) in child malnutrition management. Methods: An exploratory cross-sectional study was conducted to explore barriers to providing adequate nutrition care as perceived by the healthcare providers (HCPs) in the child malnutrition clinic at a Children’s University Hospital in Egypt. Participants were selected using the purposive sampling technique. All HCPs in the clinic were included (two male physicians, one female physician, and two female nurses). Qualitative data were collected through in-depth interviews. The interview guide consisted of semi-structured open-ended questions. Quantitative data were the resulting scores from the scoring system used to assess the understandability and actionability of the patient education materials (PEMs) that are available in the clinic. The Patient Education Materials Assessment Tool for Printable Materials (PEMAT-P) for the scoring. Statistical analysis: The thematic content analysis technique was employed for qualitative data. The percent score was generated for the PEM actionability and understandability for quantitative data. Results: Most common child malnutrition conditions encountered by HCPs were nutritional deficiencies. Barriers to the delivery of adequate nutrition care to children were physician-centered: limited nutrition education in the medical school, health system-centered: an insufficient number of HCPs, lack of nutritional supplements, lack of patient education materials (PEMs) that suit the characteristics of the served community, lack of updated standard of practice (SOP) and guidelines, inadequate nutrition training of HCPs, and insufficient time for each patient, and caregivers-centered: the low socioeconomic status and false cultural, nutritional beliefs. Conclusion: There are different barriers to adequate nutrition care for child malnutrition in low-resource healthcare settings. Mainly nutritional deficiencies. Most of the barriers were health system-related in the form of insufficient resources (shortage of workforce; concerning the high caseload, nutritional supplements, and PEMs) and inadequate management of resources (lack of skill-based training, lack of updated SOP and guidelines, and lack of properly designed PEMs that facilitate communication with the target caregivers). Keywords: Malnutrition; Low-resource healthcare settings; Skill-based training; Updated standard of practice; Guidelines; Nutritional supplements; Patient education materials